Community dialectical behaviour therapy for emotionally dysregulated adults with intellectual disabilities. Issue 3 (29th April 2014) - Baillie, Aubrey; Slater, Sean
Abstract : Purpose: – The purpose of this paper is to reflexively examine the challenges of implementing a community dialectical behaviour therapy (DBT) service for adults with intellectual disabilities (ID) and describes the practical lessons learned about how to maximise the effectiveness of DBT with this client group. Design/methodology/approach: – A brief overview of DBT is provided and reference is made to literature which highlights the potential benefits of providing a DBT service to clients with an ID. This is followed by a discussion of the clinical presentation of the clients receiving DBT in the service that is the focus of this case study. Using a reflexive approach, a detailed discussion follows of the challenges faced in implementing a community DBT service for the clients served. Findings: – Solutions to a variety of challenges faced in four years of service delivery are described, key lessons learned are highlighted, together with issues meriting further research. Research limitations/implications: – This case study and its implications are limited to community DBT services. Another limitation is that, although outcome data have been collected over the past two years, the dataset is not yet large enough to draw statistical conclusions. Practical implications: – The paper describes adaptations to treatment structure and strategy which the authors believe are necessary to improve treatment outcomes in community DBT services for adults with ID. In particular, the practical experience suggests that a didactic approach to teaching DBT skills is not effective and should be replaced by the "community of learners" approach that involves the trainer contingently responding to client input. Pre-set lesson plans inhibit the trainers' ability to respond contingently. Originality/value: – The existing literature on providing a DBT service for people with an ID has principally focused on providing a rationale for providing this type of intervention, and on assessing outcomes. Given that this is still a relatively new type of provision for this client group, a detailed examination of process issues is called for.